2011
DOI: 10.1002/hed.21869
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective A1‐adenosine‐agonist (2‐chloro‐N6‐cyclopentyladenosine) and reduction of flap necrosis in adipocutaneous flaps in rats

Abstract: Our data show that reduction of flap necrosis can be achieved both with and without ischemic periods by intravenous administration of CCPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…In 2005, Hu et al demonstrated similar effects already in rat hearts by a selective blocking of adenosine receptors in tissue and on neutrophils by the administration of 8‐phenyl‐theophyllin. The interaction of fewer cells and the inhibition of neutrophil activity in adenosine groups led to a significant reduction of flap necrosis with improved survival of the tissue, as we showed in our previous study . Our data demonstrate that the adenosine receptor system within the neutrophils is most likely of more importance in the context of I/R injury than expected, but it remains unclear why this happens specifically in healthy subcutis (Table ).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…In 2005, Hu et al demonstrated similar effects already in rat hearts by a selective blocking of adenosine receptors in tissue and on neutrophils by the administration of 8‐phenyl‐theophyllin. The interaction of fewer cells and the inhibition of neutrophil activity in adenosine groups led to a significant reduction of flap necrosis with improved survival of the tissue, as we showed in our previous study . Our data demonstrate that the adenosine receptor system within the neutrophils is most likely of more importance in the context of I/R injury than expected, but it remains unclear why this happens specifically in healthy subcutis (Table ).…”
Section: Discussionsupporting
confidence: 75%
“…The interaction of fewer cells and the inhibition of neutrophil activity in adenosine groups led to a significant reduction of flap necrosis with improved survival of the tissue, as we showed in our previous study. 14 Our data demonstrate that the adenosine receptor system within the neutrophils is most likely of more importance in the context of I/R injury than expected, but it remains unclear why this happens specifically in healthy subcutis (Table 3). On the other hand, a significant reduction in the number of plasma cells can be verified, in addition to the changes of the amount of neutrophils in flaps adjacent to localization A.…”
Section: Subcutismentioning
confidence: 61%
See 2 more Smart Citations
“…Adenosine can inhibit norepinephrine release and attenuate the activation of the renin-angiotensin system, meaning it can prohibit cardiomyocyte hypertrophy. 2-Chloro-N6 cyclopentyladenosine (CCPA) is warranted as an adenosine A 1 receptor agonist [19,20]. We speculate that CCPA may ameliorate cardiac hypertrophy.…”
Section: Introductionmentioning
confidence: 99%